Evaluation of the impact of transportation changes on air quality. (August 2015) - Titos, G.; Lyamani, H.; Drinovec, L.; Olmo, F.J.; Močnik, G.; Alados-Arboledas, L.
Abstract: Transport regulation at local level for the abatement of air pollution has gained significant traction in the EU. In this work, we analyze the effect of different transportation changes on air quality in two similarly sized cities: Granada (Spain) and Ljubljana (Slovenia). Several air pollutants were measured at both sites before and after the implementation of the changes. In Ljubljana, a 72% reduction of local black carbon (BC), from 5.6 to 1.6 μg/m 3, was observed after the restriction was implemented. In Granada, statistically significant reductions of 1.3 μg/m 3 (37%) in BC and of 15 μg/m 3 (33%) in PM10 concentrations were observed after the public transportation re-organization. However, the improvement observed in air quality was very local since other areas of the cities did not improve significantly. We show that closing streets to private traffic, renewal of the bus fleet and re-organization of the public transportation significantly benefit air quality. Highlights: Effect of air quality plans on black carbon concentrations has been evaluated. Black carbon concentrations were reduced by limiting traffic to public transport. Reorganization of bus routes and renewal of the bus fleet improve air quality.